2013
DOI: 10.1080/15321819.2012.741087
|View full text |Cite
|
Sign up to set email alerts
|

Differential Modulation of Phenotypic Composition of Hiv-Infected and -Uninfected PBMCS During Cryopreservation

Abstract: This article was designed to determine variations in phenotypic composition of fresh and frozen PBMCs for assessing utility of cryopreserved PBMCs for phenotypic assays. Relative percentages of effector memory cells increased significantly as against percentages of naïve cells which showed significant decrease after cryopreservation in HIV-uninfected samples. These differences were not significant in HIV-infected individuals. There was no significant difference in the expression of activation markers in fresh … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 23 publications
2
6
0
Order By: Relevance
“…Percentages of total T regs , measured by the phenotype CD4 + CD25 + CD127 low/− , were not affected by cryopreservation of PBMC, which agreed with previous reports (Van Hemelen et al, 2010,Venet et al, 2010,Shete et al, 2013). These percentages were also well correlated with those measured by the phenotype CD4 + CD25 + FoxP3 + , regardless of types of the samples and HIV status.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Percentages of total T regs , measured by the phenotype CD4 + CD25 + CD127 low/− , were not affected by cryopreservation of PBMC, which agreed with previous reports (Van Hemelen et al, 2010,Venet et al, 2010,Shete et al, 2013). These percentages were also well correlated with those measured by the phenotype CD4 + CD25 + FoxP3 + , regardless of types of the samples and HIV status.…”
Section: Discussionsupporting
confidence: 93%
“…Several studies have examined percentages of total T regs before and after cryopreservation, with some showing lower percentages after cryopreservation (Elkord, 2009,Sattui et al, 2012) and others finding no difference (Van Hemelen et al, 2010,Venet et al, 2010,Shete et al, 2013). To our knowledge no study has evaluated the effect of cryopreservation on different subsets of T regs .…”
Section: Introductionmentioning
confidence: 99%
“…Some published studies have reported that cryopreservation and subsequent thawing did not alter the proportion of T cell subsets, but levels of CD62L expression of CD4 + T cells were reduced on thawed cells but restored if these cells were cultured overnight after thawing [19][20][21]. Shete et al reported differential modulation of phenotypic composition of HIV-infected and HIVuninfected peripheral blood mononuclear cells during cryopreservation, and they reported a significant decrease in CD62L-expressing CD8 + cells [22]. These reports indicated the lability of CD62L in response to cryopreservation [22].…”
Section: Discussionmentioning
confidence: 99%
“…Shete et al reported differential modulation of phenotypic composition of HIV-infected and HIVuninfected peripheral blood mononuclear cells during cryopreservation, and they reported a significant decrease in CD62L-expressing CD8 + cells [22]. These reports indicated the lability of CD62L in response to cryopreservation [22]. Additionally, several studies have indicated that in vitro generation and maintenance of T memory-like cells require antigenic restimulation and supplementation of cytokines such as Interleukin (IL)-2, IL-7 and IL-15 during cell culture [23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…With this approach the inherent variability associated with study participants would be removed and the study could focus on differences that might be associated with technical aspects of the procedures. Overnight shipping of fresh mucosal specimens can be confounded by weather-associated delays, and there is also concern about the changes in cell phenotype that might be introduced by cryopreservation [ 13 ]. Further work will be needed to evaluate the impact of cryopreservation on the phenotype of cells isolated from various tissue compartments.…”
Section: Discussionmentioning
confidence: 99%